Prevalence of Sacroiliitis in Inflammatory Bowel Disease Using a Standardized Computed Tomography Scoring System. Issue 5 (2nd April 2018) - Chan, Jonathan; Sari, Ismail; Salonen, David; Silverberg, Mark S.; Haroon, Nigil; Inman, Robert D.
Abstract : Objective: There is an increasing emphasis on the early identification and treatment of ankylosing spondylitis (AS) of which the hallmark is sacroiliitis. Patients with inflammatory bowel disease (IBD) are at increased risk of AS and often receive computed tomography (CT) scans of their abdomen, affording clinicians the opportunity to determine the presence of sacroiliitis. Previous studies using CT have relied only on the radiologist's gestalt or a nonvalidated adaptation of the modified New York criteria. Our aim is to assess the prevalence of sacroiliitis in IBD using a validated screening tool and to determine how frequently these patients are referred for rheumatologic evaluation. Methods: Patients with IBD were recruited from an IBD clinic. Control patients were recruited from a urology clinic and were confirmed to be without back pain, spondylitis, psoriasis, colitis, or uveitis by chart review. CT scans were read by 2 blinded readers and sacroiliitis was defined by the presence of ankylosis or a total erosion score of ≥3. Results: CT scans were available in 233 Crohn's disease (CD) patients, 83 ulcerative colitis (UC) patients, and 108 control patients, and sacroiliitis was seen in 15%, 16.9%, and 5.6% of patients, respectively. The prevalence was higher in patients with IBD than in controls ( P = 0.007), with no significant difference between CD and UC patients. Of the 49 IBD patients found to have sacroiliitis by CT scan, only 5 had been referred to a rheumatologist. Conclusion: There is a 3‐fold higher prevalence of sacroiliitis in IBD compared with controls. Despite a growing awareness of this increased prevalence, many patients are not referred to a rheumatologist.